2015
DOI: 10.1002/ange.201503392
|View full text |Cite
|
Sign up to set email alerts
|

Access to Stable Metalloradical Cations with Unsupported and Isomeric Metal–Metal Hemi‐Bonds

Abstract: + and trans-3C + in one crystal is unprecedented in the field of dinuclear metalloradical chemistry.The work suggests that more stable metalloradicals of metal-metal hemi-bonds may be accessible by using metal carbonyls together with large and weakly coordinating polyfluoroaluminate anions.Itisoffundamental importance to understand the nature of metal-metal bonds.[1] Compared with those supported by bridging ligands,unsupported metal-metal bonds are simpler and have attracted particular interest.[2] Understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…F. R. Knight et al investigated the nature of E···Z (E, Z = S, Se, and Te) interactions in peri‐substituted chalconium acenaphthene and naphthalene salts, and they found that the E···Z interaction has both attractive and repulsive interactions with the location of p‐type lone pairs being correlated to the ability of the frontier orbitals to take part in these interactions . Recently, a number of interesting radical cations, such as 1,8‐bis(phenylselenyl) naphthalene [Nap(SePh) 2 ] •+ , 1,8‐bis(phenyl‐sulfur) naphthalene [Nap(SPh) 2 ] •+ , and 1‐(phenylselenyl)−8‐ (phenylsulfanyl) naphthalene [Nap(SPh)(SePh)] •+ , that feature Se∴Se, S∴S, and S∴Se 3e σ‐bonds have been stabilized by Xinping Wang et al Their structures have been investigated by ultraviolet‐visible (UV) spectroscopy, electron paramagnetic resonance (EPR), and single‐crystal X‐ray diffraction in conjunction with density functional theory (DFT) calculations on the orbital analysis. While, the following questions still need to be explored: (1) Which is dominant in E···E' attractive interactions, electrostatic or covalent interactions?…”
Section: Introductionmentioning
confidence: 99%
“…F. R. Knight et al investigated the nature of E···Z (E, Z = S, Se, and Te) interactions in peri‐substituted chalconium acenaphthene and naphthalene salts, and they found that the E···Z interaction has both attractive and repulsive interactions with the location of p‐type lone pairs being correlated to the ability of the frontier orbitals to take part in these interactions . Recently, a number of interesting radical cations, such as 1,8‐bis(phenylselenyl) naphthalene [Nap(SePh) 2 ] •+ , 1,8‐bis(phenyl‐sulfur) naphthalene [Nap(SPh) 2 ] •+ , and 1‐(phenylselenyl)−8‐ (phenylsulfanyl) naphthalene [Nap(SPh)(SePh)] •+ , that feature Se∴Se, S∴S, and S∴Se 3e σ‐bonds have been stabilized by Xinping Wang et al Their structures have been investigated by ultraviolet‐visible (UV) spectroscopy, electron paramagnetic resonance (EPR), and single‐crystal X‐ray diffraction in conjunction with density functional theory (DFT) calculations on the orbital analysis. While, the following questions still need to be explored: (1) Which is dominant in E···E' attractive interactions, electrostatic or covalent interactions?…”
Section: Introductionmentioning
confidence: 99%
“…The concept of the odd-electron σ-bond was first proposed by Pauling 8 , and species with these intriguing bonds have been recognized as important intermediates in chemistry and biochemistry [9][10][11][12][13][14][15][16][17][18][19][20][21] . A number of radicals with a one-electron [22][23][24][25] or three-electron σ-bond 12,[26][27][28][29][30][31][32] have been isolated and structurally studied (Fig. 1).…”
mentioning
confidence: 99%